RANCANG ULANG SISTEM PENDINGIN PADA MESIN FREEZER MULTIFUNGSI - Mukhammad Zidan N; George Endri Kusuma; Projek Priyonggo Sumangun L (Politeknik Perkapalan Negeri Surabaya, 2023)
Previous research was the beginning of the manufacture a multifunctional freezer, a machine that has two functions for cooling and drying and is aimed at preserving fish both dried and cooled. The evaporator on the machine is used for cooling the fish in the refrigerator. The cooling process has a weakness in the cooling system where the temperature in the chamber can’t reach a temperature below 0°C when the load is given above 0,5kg, and its cooling rate is less efficient so that the process of temperature reduction in a chamber given the load variation has a long enough time, so it can be concluded that the performance of the chiller is less optimal. In this final project, a cooling system redesign is carried out on a multifunctional freezer machine, as well as a capillary tube with a diameter of 0,31 inches and a length of 1,5 meters. Test results were obtained with weight variations of 0,5kg, 2kg, and 3kg. Average cooling speed of 0,255 kJ/s, chill room temperature of 2,7°C to -6°C, and the best coefficient of performance are obtained from the test results at a weight of 3kg with a COP value of 6,609 at 30 minutes and 5,133 at a test time of 60 minutes or 1 hour of operation of the multifunction freezer.